Long‐Term Loss of Response in Proton Pump Inhibitor‐Responsive Esophageal Eosinophilia Is Uncommon and Influenced by CYP2C19 Genotype and Rhinoconjunctivitis. (November 2015) - Molina‐Infante, Javier; Rodriguez‐Sanchez, Joaquin; Martinek, Jan; van Rhijn, Bram D; Krajciova, Jana; Rivas, Maria D; Barrio, Jesus; Moawad, Fouad J; Martinez‐Alcalá, Carmen; Bredenoord, Albert J; Zamorano, Jose; Dellon, Evan S
Abstract : OBJECTIVES: Proton pump inhibitor‐responsive esophageal eosinophilia (PPI‐REE) is diagnosed in at least one‐third of patients with suspected eosinophilic esophagitis (EoE). We aimed to evaluate the durability and factors influencing long‐term efficacy of PPI therapy. METHODS: Retrospective multicenter cohort study of patients with PPI‐REE who had at least 12 months of follow‐up. PPI therapy was tapered to the lowest dose, which maintained clinical remission. Primary outcomes were the proportion of patients with loss of histological response (<15 eos/HPF) and predictors of loss of response. CYP2C19 polymorphisms were determined from blood samples in a subset of patients. RESULTS: Seventy‐five PPI‐REE patients were included (mean follow‐up 26 months (12–85)), of whom fifty‐five (73%) had sustained histological remission on low‐dose PPI therapy. Loss of response was significantly higher in those patients with a CYP2C19 rapid metabolizer genotype (36% vs. 6%, P  = 0.01) and with rhinoconjunctivitis (40% vs. 13%, P  = 0.007). On the multivariate analysis, a CYP2C19 rapid metabolizer genotype (odds ratio (OR) 12.5; 95% confidence interval (CI): 1.3–115.9) and rhinoconjunctivitis (OR 8.6; 95% CI: 1.5–48.7) were independent predictors of loss of response. Among relapsing patients, eosinophilia was limited to the distal esophagus in 14/20 (70%). Nine of ten relapsers, with distal eosinophilia, all showing a CYP2C19 rapid metabolizer genotype, regained histological remission after PPI dose intensification. CONCLUSIONS: Most PPI‐REE patients remain in long‐term remission on low‐dose PPI therapy. CYP2C19 rapid metabolizer genotypes and rhinoconjunctivitis were independent predictors of loss of response to PPI, but patients frequently responded to PPI dose escalation.